Saliva: A Cutting Edge in Diagnostic Procedures. (25th May 2014) - Sindhu, Senthamil; Jagannathan, Nithya
Abstract : The ability to monitor the health and disease status of the patient through saliva is a highly desirable goal for the health professionals. Considering the microconcentration of salivary constituents, saliva is explored to be diagnostic tool as it also meets the demands for an inexpensive, noninvasive and easy to use screening method. The incorporation of salivary diagnostics into clinical practice is gaining reality and will be of diagnostic value in the prospective future. The investigative use of saliva is not being applied only in dental health but also in various other systemic disorders. The advent of molecular techniques is gaining attention and this has triggered its application as a specific and sensitive biomarker in proteomics, genomics, and transcriptomics. This review discusses the basics of salivary diagnostics, expectoration techniques, and its application in various local and systemic disorders.